Reading and writing workshop for Youth and Adult Education students: the relevance of the school library as a pedagogical resource - Azevedo, Anderson L. (Biblioteca Escolar em Revista, 2022)
The purpose of this article is to present an experience report on the development of the Reading and Writing Workshop for students of Youth and Adult Education, at Joaquim Venâncio Polytechnical School of Health Library - Emília Bustamante, from Oswaldo Cruz Foundation in Rio de Janeiro. To this end, an overview of illiteracy in Brazil appears first, according to information from IBGE in 2019 and the Law on National Education Guidelines and Framework determinations to mitigate this social gap. Then, the concepts of EJA (Youth and adult Education), the importance of reading and writing and the definition of the school library are ordered. Finally, the reports from the Portuguese language teacher, the course coordinator and the librarians who followed the development of the Workshop and the results obtained are analyzed. According to these professionals, it was observed that the participating students showed advances in performance inside and outside the classroom, with a significant improvement in interpretation of texts, writing and even in diction. In conclusion, the experience proves the importance of reading and writing in the individual's life in society and the impact of the school library as a pedagogical resource in the development of literacy capacity and in the formation of a critical person, who seeks to expand his existential experiences according to his reality and experiences.